Electrode mixture, and electrode layer and solid-state battery using the same
The electrode composite material with titanium niobium oxide and a sulfide solid electrolyte addresses the interface issues in solid-state batteries, enhancing charge/discharge efficiency by optimizing particle size and surface area, ensuring effective battery performance.
Patent Information
- Application Number
- JP2021505944
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-13
- Filing Date
- 2020-09-14
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-09-14
AI Technical Summary
Titanium niobium composite oxide, despite its high theoretical capacity, exhibits unsatisfactory performance when combined with a solid electrolyte due to unknown reaction interface characteristics, potentially leading to non-functional batteries.
An electrode composite material comprising a titanium niobium composite oxide with a specific BET specific surface area and particle size distribution, combined with a sulfide solid electrolyte containing lithium, phosphorus, and sulfur elements, to ensure effective lithium ion conduction and charge/discharge efficiency in solid-state batteries.
The proposed electrode composite material achieves excellent charge/discharge efficiency in solid-state batteries by optimizing the interface contact and preventing resistance, ensuring functional and efficient battery operation.
Smart Images

Figure 0007606448000002 
Figure 0007606448000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode mixture that can be suitably used for, for example, solid-state batteries, particularly all-solid-state lithium secondary batteries. [Background technology]
[0002] Electrodes used in all-solid-state lithium secondary batteries are generally manufactured by mixing particles of an active material made of a material capable of inserting lithium ions by charging with a binder, a conductive material, and a solvent, applying the resulting mixture to the surface of a current collector, drying it to form a coating film, and then pressing it. Currently, most of the electrodes for batteries on the market use carbon materials (also called "graphite") as the active material. However, when carbon materials are used as electrode active materials, there have been accidents in which the electrodes short-circuit or the battery deforms, causing smoke or fire, and the material is not sufficiently safe. In addition, the theoretical limit has already been reached in terms of capacity, and the development of new electrode active materials is required.
[0003] In recent years, research has been conducted on metal composite oxides as an alternative active material to carbon materials, and titanium oxide has been attracting particular attention. It has been reported that batteries using titanium oxide as an electrode active material are capable of stable rapid charging and discharging. Among these, lithium titanium composite oxide Li[Li 1 / 3 Ti 5 / 3 ]O4(LTO) is a material that can absorb and release lithium ions without changing the structure or size of the crystal lattice, and has attracted attention as an electrode active material for high-reliability lithium-ion batteries and has been put to practical use. However, compared to graphite-based electrodes, LTO electrodes have smaller capacities per mass and volume, and because their electrode potential is high, the operating voltage of the battery is low. Therefore, in order to increase the energy density while ensuring safety, there is a demand for higher-capacity metal composite oxide electrode materials. Titanium-niobium composite oxides, typified by TiNb2O7, have a high theoretical capacity per mass and per volume that is approximately twice that of LTO, and are attracting attention as a material that is expected to achieve a high energy density (charge / discharge capacity).
[0004] Regarding the technology using titanium-niobium composite oxide as an active material, for example, Patent Document 1 describes a titanium-niobium composite oxide having a BET specific surface area of 0.18 m 2 / g or more as an active material, a titanium-niobium composite oxide such as TiNb2O7 is disclosed.
[0005] Patent Document 2 discloses an active material for a battery, which comprises secondary particles formed by agglomeration of primary particles of an active material, the primary particles of the active material containing a niobium composite oxide such as a titanium-niobium composite oxide and having a compressive fracture strength of 10 MPa or more, and a carbon material phase formed on at least a part of the surface of the secondary particles.
[0006] Moreover, Patent Document 3 discloses a non-aqueous electrolyte battery using a negative electrode having a negative electrode active material layer containing particles of a niobium titanium-containing composite oxide. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-287496 A [Patent Document 2] JP 2015-88467 A [Patent Document 3] JP 2016-219355 A Summary of the Invention [Problem to be solved by the invention]
[0008] As mentioned above, titanium-niobium composite oxide has a high theoretical capacity and is a noteworthy material as an active material, but even if it exhibits excellent battery performance when used with a liquid electrolyte, its characteristics when used in combination with a solid electrolyte are unknown. Since the state of the reaction interface is different between liquid electrolytes and solid electrolytes, not only may the expected battery characteristics not be obtained, but it may also not function as a battery in the first place.
[0009] Therefore, the present invention relates to an electrode composite material using a titanium-niobium composite oxide as an active material in combination with a solid electrolyte, and aims to provide a new electrode composite material that can provide excellent battery characteristics, particularly excellent charge / discharge efficiency, when used to construct a solid-state battery. [Means for solving the problem]
[0010] The present invention relates to an electrode mixture comprising a sulfide solid electrolyte containing lithium (Li), phosphorus (P) and sulfur (S) and an active material, The active material has the general formula Ti 1±α Nb 2±β O 7±γ (wherein, 0≦α<1, 0≦β<2, 0≦γ<0.3), The active material has a particle diameter D at which the volume cumulative particle diameter becomes 50% based on a volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method, relative to a BET specific surface area (also referred to as "BET specific surface area" or "BET") analyzed by a multilayer adsorption theory from a gas adsorption isotherm. 50 ("D 50 ") ratio (D 50 (μm) / BET(m 2 / g) is 0.005 or more and 5.0 or less. Effect of the Invention
[0011] The electrode mixture proposed by the present invention has a BET specific surface area of titanium-niobium composite oxide as an active material. 50 Ratio of (D 50 (μm) / BET(m 2 / g) is adjusted to a predetermined range, while for the solid electrolyte, a sulfide solid electrolyte containing lithium (Li), phosphorus (P) and sulfur (S) is used to form an electrode mixture, and when a solid battery is formed using the electrode mixture, excellent battery characteristics, particularly excellent charge / discharge efficiency, can be obtained. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a diagram showing X-ray diffraction patterns obtained by measuring the solid electrolytes used in Examples 1 to 5 and Comparative Example 1 by an X-ray diffraction method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.
[0014] <This electrode composite material> The electrode mixture according to one embodiment of the present invention (hereinafter referred to as the "electrode mixture") has the general formula Ti 1±α Nb 2±β O 7±γ (wherein 0≦α<1, 0≦β<2, 0≦γ<0.3), and a sulfide solid electrolyte (hereinafter referred to as "the present solid electrolyte").
[0015] (This active material) The active material has the general formula (1): Ti 1±α Nb 2±β O 7±γ (wherein 0≦α<1, 0≦β<2, 0≦γ<0.3) is sufficient. Among these, it is preferable to use a titanium-niobium composite oxide having the same crystal structure as TiNb2O7, i.e., a monoclinic TiNb2O7 crystal structure.
[0016] In the general formula (1), α is preferably 0 or more and less than 1, more preferably 0.3 or less, and even more preferably 0.1 or less. In the general formula (1), β is preferably 0 or more and less than 2, more preferably 1 or less, and even more preferably 0.5 or less. In the general formula (1), γ is preferably 0 or more and less than 0.3, more preferably 0.2 or less, and even more preferably 0.1 or less.
[0017] In addition, in the present active material, a part of the Ti or Nb element in general formula (1) may be replaced with B, Na, Mg, Al, Si, S, P, K, Ca, Ba, Mo, W, Sr, Cr, Mn, Fe, Co, Ni, Pb, etc.
[0018] This active material has a D 50 Ratio of (D 50 (μm) / BET(m 2 / g)) is preferably 0.005 or more and 5.0 or less. The ratio of the active material (D 50 (μm) / BET(m 2 By setting the ratio (ratio) of the solid electrolyte to 0.005 or more, it is possible to prevent an increase in contact resistance with the solid electrolyte and a decrease in lithium ion conduction (battery performance), which is preferable. On the other hand, by setting the ratio (ratio) of the solid electrolyte to 5.0 or less, it is possible to maintain a suitable contact area with the solid electrolyte even when the particle size is relatively large, and it is preferable to ensure lithium ion conduction (battery performance) between the solid electrolyte and the active material. From this viewpoint, the above ratio (D 50 (μm) / BET(m 2 / g)) is more preferably 0.1 or more, and even more preferably 0.2 or more, while it is more preferably 4.0 or less, and even more preferably 3.0 or less.
[0019] This active material is D 50 It is preferable that the thickness is 0.1 μm or more and 8.0 μm or less. D of this active material 50If the specific surface area is 0.1 μm or more, the increase in the number of contacts with the solid electrolyte caused by the increase in the specific surface area can be suppressed, and the increase in contact resistance can be suppressed. On the other hand, if the specific surface area is 8.0 μm or less, the effect of expansion and contraction can be reduced, and the contacts with the solid electrolyte can be secured, which is preferable. From this viewpoint, the D 50 It is more preferable that the thickness is 0.5 μm or more, and more preferably 1.0 μm or more, while it is more preferable that the thickness is 5.0 μm or less, and more preferably 4.5 μm or less. D of this active material 50 can be adjusted by changing the firing conditions, crushing conditions and pulverization conditions, but is not limited to these adjustment methods.
[0020] In addition, D 50 This means the 50% volume cumulative particle size, that is, the diameter that is 50% cumulative from the finest cumulative percentage of the particle size measurements converted into volume on a volume-based particle size distribution chart. D of this active material 50 can be measured by the method shown in the Examples.
[0021] The BET specific surface area of this active material is 1.0m 2 / g or more 20m 2 It is preferable that the molecular weight is not more than 1 / g. The BET specific surface area of this active material is 1.0m 2 If the surface area is 20m / g or more, lithium ion conduction (battery performance) can be ensured by maintaining appropriate surface contact when the active material and the solid electrolyte are mixed, which is preferable. 2 / g or less is preferable from the viewpoints of suppressing contact resistance with the solid electrolyte, preventing peeling from the solid electrolyte during charging and discharging, and preventing a decrease in lithium ion conduction (battery performance). From this viewpoint, the BET specific surface area of the present active material is, among others, 1.1 m 2 / g or more is more preferable, and among them, 1.2m 2 / g or more is more preferable. 2 / g or less is more preferable, and among them, 5.0m 2 It is more preferable that the molecular weight is not more than 1 / g. The BET specific surface area of the present active material can be adjusted by changing the firing conditions, crushing conditions and pulverization conditions, but is not limited to these adjustment methods.
[0022] The BET specific surface area of the present active material is a BET specific surface area analyzed by multilayer adsorption theory from a gas adsorption isotherm, and can be measured by the method shown in the Examples.
[0023] This active material is defined as the particle size at which the cumulative particle size by volume is 90% based on the volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method. 90 The particle diameter at which the cumulative particle diameter by volume becomes 10% is D 10 In this case, D 90 and D 50 and D 10 Relationship with (D 90 (μm)-D 10 (μm) / D 50 (μm)=0.8~1.5 It is more preferable to satisfy
[0024] (D 90 (μm)-D 10 (μm) / D 50 (μm) indicates the degree of variation in particle size, and if the value of the above relational expression is 0.8 or more, the active material has a particle size distribution with some variation, which makes the surface contact when mixed with the solid electrolyte more uniform and ensures uniform lithium ion conduction (battery performance), which is preferable. On the other hand, if the value of the above relational expression is 1.5 or less, it is preferable from the viewpoint of suppressing excessive variation in particle size of the active material, maintaining surface contact when mixed with the solid electrolyte, and maintaining lithium ion conduction (battery performance). From this viewpoint, the value of the above relational expression is more preferably 0.9 or more, and even more preferably 1.0 or more, while it is more preferably 1.45 or less, and even more preferably 1.4 or less.
[0025] D of this active material 90 is preferably 1.5 μm or more, and more preferably 2.5 μm or more, while it is preferably 10 μm or less, and more preferably 7 μm or less. D of this active material 10 is preferably 0.1 μm or more, and more preferably 0.8 μm or more, while it is preferably 3 μm or less, and more preferably 2 μm or less. D of this active material 90 and D. 10 The adjustment and measurement methods are as described above for D 50 is the same as:
[0026] This active material has an average particle size D calculated by software analysis of particles in a scanning electron microscope image. SEM With respect to the particle size D 50 Ratio of (D 50 (μm) / D SEM (μm) is preferably 1.0 or more and 3.5 or less. D 50 The value of D can be considered as the average particle size when aggregated particles are regarded as a single particle (aggregated particle). The less aggregated the particle, the closer it is to monodispersion. 50 The value of is usually small. On the other hand, D SEM is the average particle size calculated by extracting a number of primary particles from an image taken with a SEM (scanning electron microscope) as described below. 50 / D SEM ) can be regarded as the degree of aggregation, and if there are many aggregates, D 50 D SEM When the aggregated state becomes smaller, the D 50 D SEM The ratio (D 50 / D SEM ) approaches 1. On the other hand, the ratio (D 50 / D SEM ) is more preferably 3.0 or less, and even more preferably 2.0 or less.
[0027] This active material is D SEM It is preferable that the thickness is 0.1 μm or more and 3.0 μm or less. D of this active material SEM If the thickness is 3.0 μm or less, the influence of expansion and contraction can be reduced, and the contact with the solid electrolyte in the solid battery electrode can be secured. SEM If the specific surface area is 0.1 μm or more, an increase in the number of contact points with the solid electrolyte caused by an increase in the specific surface area can be suppressed, and an increase in contact resistance can be suppressed. From this viewpoint, the D SEM It is more preferable that the thickness is 2.5 μm or less, and more preferably 2.2 μm or less, while it is more preferable that the thickness is 1.0 μm or more, and more preferably 1.4 μm or more. D of this active material SEM can be adjusted by changing the firing temperature, changing the titanium oxide and niobium oxide raw materials, or changing the crushing and pulverizing conditions of the raw materials, but is not limited to these adjustment methods. D SEM can be measured by the method shown in the Examples.
[0028] (This solid electrolyte) The present solid electrolyte is preferably a sulfide solid electrolyte containing lithium (Li), phosphorus (P) and sulfur (S), and preferably has lithium ion conductivity. The solid electrolyte may be any of a crystalline material, a glass ceramic, and a glass.
[0029] The solid electrolyte may be a compound having an Argyrodite-type crystal structure, that is, a compound having a crystal phase with an Argyrodite-type structure. Examples of such sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiHa (where "Ha" represents one or more halogen elements), Li2S-P2S5-P2O5, Li2S-Li3PO4-P2S5, Li3PS4, Li4P2S6, and Li 10 GeP2S 12, Li 3.25 Ge 0.25 P 0.75 S4, Li7P3S 11 , Li 3.25 P 0.95 S4, Li 7-x PS 6-x Ha x ("Ha" represents one or more halogen elements, where 0.2 < x < 2.0 or 0.2 < x < 1.8.) Examples thereof include. Also, compositions having a Li-Si-P-S type crystal structure described in International Publication No. 2013 / 099834 pamphlet and International Publication No. 2015 / 001818 pamphlet, and compositions having a structural framework of Li7PS6 and having a part of P substituted with Si can also be mentioned.
[0030] This solid electrolyte is preferably powdery particles, and regarding its particle size, D 50 is preferably 0.1 μm or more and 10 μm or less. For D of this solid electrolyte 50 If it is 0.1 μm or more, it is preferable because an increase in resistance due to an increase in the surface of the solid electrolyte particles and difficulty in mixing with the active material do not occur. On the other hand, if D of this solid electrolyte 50 is 10 μm or less, it is preferable because it becomes easier for this solid electrolyte to enter the gaps between the active materials, and the contact points and contact areas become larger. From such a viewpoint, D of this solid electrolyte 50 is preferably 0.1 μm or more and 10 μm or less, and more preferably 0.3 μm or more or 7 μm or less, and particularly preferably 0.5 μm or more or 5 μm or less among them. For D of this solid electrolyte 50 can be measured by the method shown in the examples. For D of this solid electrolyte 50 can be adjusted by changing the crushing conditions and grinding conditions. However, it is not limited to these adjustment methods.
[0031] For D of this solid electrolyte 50 is the D of the positive electrode active material 50 or the D of the negative electrode active material 50It is preferable that the ratio is 1% or more and 100% or less. This solid electrolyte D 50 However, the positive electrode active material D 50 Or negative electrode active material D 50 If the content is 1% or more, the active materials can be filled without gaps, which is preferable, whereas if the content is 100% or less, the active material ratio in the electrode becomes high, which is preferable from the viewpoint of increasing the energy density of the battery. From this perspective, the D 50 is the positive electrode active material D 50 Or negative electrode active material D 50 Of these, it is preferably 1% or more and 100% or less, more preferably 3% or more or 50% or less, and even more preferably 5% or more or 30% or less.
[0032] (This electrode composite material) In the present electrode composite, with regard to the mixing ratio of the present active material and the present solid electrolyte, from the viewpoint of good contact at the interface between the active material and the solid electrolyte, it is preferable to mix the two so that the ratio (Nb / P) of the niobium (Nb) content (mol) of the present active material to the phosphorus (P) content (mol) of the solid electrolyte is 1 or more and 173 or less.
[0033] The present electrode mixture may contain, in addition to the present active material and the present solid electrolyte, a binder, a conductive material, graphite as another electrode active material, and other materials as necessary.
[0034] The binder is not particularly limited as long as it is a material that can be used for electrodes. For example, polyimide, polyamide, polyamideimide, etc. can be mentioned. These may be used alone or in combination of two or more. Furthermore, binders other than these may be used in combination. Details of the binder may be the same as known binders, and therefore the description thereof will be omitted here. The content of the binder is preferably 1 part by mass or more and 25 parts by mass or less, and more preferably 2 parts by mass or more or 20 parts by mass or less, per 100 parts by mass of the present active material.
[0035] The conductive material is not particularly limited as long as it is a material that can be used for an electrode. For example, metal fine powder, powder of conductive carbon material such as acetylene black, etc. can be mentioned. When metal fine powder is used as the conductive material, it is preferable to use fine powder of metal having lithium ion conductivity such as Sn, Zn, Ag, and In, or alloy of these metals. When a conductive material is blended, the content of the conductive material is preferably 1 to 15 parts by mass, and more preferably 2 parts by mass or more or 10 parts by mass or less, per 100 parts by mass of the present active material.
[0036] As described above, by allowing graphite to coexist as an electrode active material in the present electrode mixture, good cycle characteristics attributable to graphite can be obtained. When graphite is blended as the electrode active material, the mixture mass ratio of this active material to graphite is preferably adjusted to 50:50 to 95:5, particularly 80:20 to 95:5.
[0037] (form) The electrode mixture may be in any form, for example, in the form of a powder or pellets. For example, the present active material, the present solid electrolyte, and other materials such as a binder, a conductive material, and another electrode active material as required may be mixed, and then the mixture may be press-molded, for example, uniaxial press-molded, to form the mixture into a pellet shape, although the method is not limited thereto.
[0038] <This electrode> The electrode mixture can be used to form a positive electrode or a negative electrode (referred to as "the electrode"). The electrode can be formed, for example, by applying the electrode mixture onto an electrode current collector. More specifically, the present electrode composite is prepared by mixing the present active material (particulate), the present solid electrolyte, a binder, a conductive material, a solvent, and if necessary, other materials such as graphite, and the present electrode composite is formed by applying the present electrode composite to the surface of a current collector made of Cu or the like, drying it, and then pressing it as necessary. Alternatively, the present active material (particulate), the present solid electrolyte, a conductive material, and if necessary, other materials such as graphite, are mixed, pressed, and then appropriately processed to produce the electrode.
[0039] After the electrode mixture is applied to the surface of the current collector, it is preferably dried in an oxygen-free atmosphere, such as a nitrogen or argon atmosphere, for 1 to 10 hours, particularly 1 to 7 hours.
[0040] <Solid-state battery> A solid-state battery (referred to as the "present solid-state battery") can be constructed using this electrode. For example, the present solid-state battery can be constructed having a positive electrode layer made of a known electrode other than the present electrode, a negative electrode layer made of the present electrode, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. In addition, the present solid-state battery can be configured to have a positive electrode layer made of the present electrode, a negative electrode layer made of a known electrode other than the present electrode, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer.
[0041] The present solid-state battery is preferably, for example, a lithium solid-state battery. The lithium solid-state battery may be a primary battery or a secondary battery, and is preferably used as a lithium secondary battery.
[0042] Here, the term "solid-state battery" includes not only solid-state batteries that do not contain any liquid or gel substance as an electrolyte, but also solid-state batteries that contain a small amount, for example, 10 mass % or less, of a liquid or gel substance as an electrolyte.
[0043] The solid electrolyte layer can be prepared, for example, by dropping a slurry consisting of a solid electrolyte, a binder, and a solvent onto a substrate and scraping it off with a doctor blade or the like, by contacting the substrate with the slurry and then cutting it with an air knife, by forming a coating film by screen printing or the like and then removing the solvent by heating and drying, etc. Alternatively, the solid electrolyte layer can be prepared by pressing a powder of the solid electrolyte into a compressed powder body by pressing or the like and then processing it appropriately.
[0044] The counter electrode layer for this electrode can be formed using, for example, an electrode material used as an electrode active material in a lithium secondary battery. In this case, when the counter electrode layer is a positive electrode layer, the electrode active material is not particularly limited as long as it functions as a positive electrode active material. For example, it may contain a lithium metal composite oxide. As the lithium metal composite oxide, a known lithium metal composite oxide can be used. As the metal in the lithium metal composite oxide, for example, both transition elements and typical elements can be used, and preferably, a transition element is used. As the lithium metal composite oxide, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium nickel cobalt manganate (Li(Ni,Co,Mn)O2), lithium manganate (LiMn2O4), and lithium nickel manganate (LiNi 0.5 Mn 1.5 O4) The structure of these oxides is not particularly limited, and may be, for example, a layered rock salt type compound or a spinel type compound. On the other hand, when the counter electrode layer is a negative electrode layer, the electrode active material is not particularly limited as long as it functions as a negative electrode active material. For example, lithium alloys such as indium lithium (InLi), graphite, silicon-based materials, etc. can be mentioned. However, the electrode active material is not limited to these.
[0045] <Explanation of terms> In this specification, when expressed as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the intention that "it is preferably greater than X" or "it is preferably less than Y". EXAMPLES
[0046] The present invention will now be described in further detail with reference to examples, although the present invention is not limited to the examples described below.
[0047] <Example 1> (Preparation of active material) D 50 Titanium oxide powder (titanium(IV), anatase type) with particle size adjusted to 2 μm, and D 50 The powder was weighed out to a molar ratio of 1:1 with niobium pentoxide powder whose particle size was adjusted to 0.6 μm. As a pretreatment for firing, these were placed in a polypropylene container, an appropriate amount of ethanol was added, and wet-disintegrated in a ball mill for 3 hours using zirconia balls with a diameter of 10 mm, which was 10 times the weight of niobium pentoxide. After that, the zirconia balls were filtered off, and the mixed raw material recovered by filtration was dried at 60°C in a dryer, and the obtained dry powder was disintegrated in a mortar. The disintegrated dry powder was placed in an alumina crucible and heat-treated at 1250°C for 24 hours in an air atmosphere using an electric furnace. After naturally cooling to less than 100°C, the recovered fired powder was pulverized in a mortar. As a posttreatment for firing, the fired powder was again placed in a polypropylene container, an appropriate amount of ethanol was added, and wet-disintegrated in a ball mill for 24 hours using zirconia balls with a diameter of 10 mm, which was 10 times the weight of niobium pentoxide. Thereafter, the zirconia balls were removed by filtration, and the sintered powder recovered by filtration was dried at 60° C. in a dryer, and the resulting dry powder was crushed in a mortar to obtain a titanium-niobium composite oxide as an active material. The titanium-niobium composite oxide obtained was analyzed by X-ray diffraction (XRD, Cu source) and identified as a single phase of TiNb2O7 with a monoclinic crystal structure. 90 , D 50 , D 10 and D. SEM was as shown in Table 1.
[0048] (Preparation of solid electrolyte) The formula is Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 A powdered sulfide compound was prepared as a solid electrolyte. 50 was 0.8 μm. D of the solid electrolyte 50 The procedure was as follows: Using an automatic sample feeder for a laser diffraction particle size distribution measurement device (Microtorac SDC, manufactured by Nikkiso Co., Ltd.), a slurry containing a solid electrolyte powder was put into a non-aqueous solvent (toluene), the flow rate was set to 50%, and 30 W of ultrasound was irradiated for 60 seconds. The particle size distribution was then measured using a laser diffraction particle size distribution measurement device MT3000II, manufactured by Nikkiso Co., Ltd., and the particle size at which the cumulative volume was 50% by volume was determined from the obtained volume-based particle size distribution chart. 50 It was decided. The solid electrolyte was also analyzed by X-ray diffraction (XRD, Cu source) to obtain an X-ray diffraction pattern and measure the peak intensity (cps) at each position. Using a Rigaku XRD device "Smart Lab", the analysis was performed under the following conditions: no exposure to air, scanning axis: 2θ / θ, scanning range: 10° to 140°, step width: 0.01°, scanning speed: 1° / min. The X-ray source was a Johansson crystal with CuKα1 radiation, and measurements were performed with a one-dimensional detector. The results are shown in Figure 1.
[0049] (Preparation of electrode mixture) The titanium-niobium composite oxide as the active material obtained as described above, a sulfide compound as the solid electrolyte, and a conductive agent (VGCF (registered trademark)) powder were mixed in a mortar in a mass ratio of 47.5:47.5:5 so that the ratio (Nb / P) of the niobium (Nb) content to the phosphorus (P) content was 44, to prepare an electrode mixture.
[0050] <Example 2> A titanium-niobium composite oxide, a solid electrolyte, and an electrode mixture were obtained in the same manner as in Example 1, except that the firing temperature in producing the titanium-niobium composite oxide as the active material was changed to 1150°C.
[0051] <Example 3> In Example 2, when preparing the titanium-niobium composite oxide as the active material, the weight of the zirconia balls having a diameter of 10 mm used for pretreatment of the sintering was changed to 20 times the weight of the niobium pentoxide. In the same manner as in Example 2, a titanium-niobium composite oxide, a solid electrolyte, and an electrode mixture were obtained.
[0052] <Example 4> In Example 1, in producing a titanium-niobium composite oxide as an active material, the weight of zirconia balls with a diameter of 10 mm used in the post-sintering treatment was changed to 20 times the weight of niobium pentoxide, and after the 10 mm zirconia balls were separated by filtration, a ball mill treatment was again carried out using zirconia balls with a diameter of 2 mm with a weight 20 times the weight of niobium pentoxide. Except for this, a titanium-niobium composite oxide, a solid electrolyte, and an electrode mixture were obtained in the same manner as in Example 1.
[0053] <Example 5> A titanium-niobium composite oxide, a solid electrolyte, and an electrode mixture were obtained in the same manner as in Example 4, except that the firing temperature in producing the titanium-niobium composite oxide as the active material was changed to 1150°C.
[0054] The titanium-niobium composite oxides obtained in Examples 2 to 5 were analyzed by X-ray diffraction (XRD, Cu source) and identified as a single phase of TiNb2O7 having a monoclinic crystal structure. 90 , D 50 , D 10 , and D SEM was as shown in Table 1.
[0055] <Comparative Example 1> A titanium-niobium composite oxide, a solid electrolyte, and an electrode mixture were obtained in the same manner as in Example 1, except that in the preparation of the titanium-niobium composite oxide as the active material, the firing temperature was changed to 1450°C. The titanium-niobium composite oxide obtained was analyzed by X-ray diffraction (XRD, Cu source) and identified as a single phase of TiNb2O7 with a monoclinic crystal structure. The specific surface area measured by the BET method using N2 adsorption was 0.80 m 2 / g, D 50 is 8.12 μm, and D SEM was 3.59 μm.
[0056] <Methods for measuring various physical properties> Various physical properties of the titanium-niobium composite oxides (active materials) obtained in the examples and comparative examples were measured as follows.
[0057] (D SEM ) The titanium-niobium composite oxide used as the active material was observed at 1000 to 10000 times magnification using a SEM (scanning electron microscope), and the primary particle diameter of the selected particles was determined from the captured images using image analysis software (Image-Pro, ver. 10.0.3, Build 6912, manufactured by Nippon Roper Co., Ltd.). In this case, the particle diameter is the measurement item name on the software, "diameter, average," and this diameter is the diameter passing through the center of gravity of the particle. Primary particles were then selected and photographed in an arbitrary field of view, and a total of 200 or more primary particles were selected to determine the particle diameter (D SEM ) was sought.
[0058] (D 90 , D50 , D 10 ) As a pretreatment, the titanium-niobium composite oxide as the active material was mixed with water and dispersed in an ultrasonic bath for 1 minute. Next, an ultrasonic probe was introduced into the ultrasonic bath and ultrasonic waves of 15 W (50 kHz) were irradiated for 90 seconds. The measurement device used was a Beckman Coulter LS13 320. 90 , D 50 , D 10 The measurement conditions were as follows: solvent refractive index: 1.33, particle permeability condition: transmission, particle refractive index: 2.4, shape: spherical, and the measurement range was 0.04 to 2000 μm. The average value of three measurements was calculated as D 90 , D 50 , D 10 It was decided.
[0059] (BET specific surface area) 1.0 g of sample (powder) was weighed into a glass cell (standard cell) for a fully automatic specific surface area measurement device MacSorb (manufactured by Mountec Co., Ltd.) and set in the autosampler. After replacing the inside of the glass with nitrogen gas, the cell was heat-treated in the nitrogen gas atmosphere at 250°C for 15 minutes. After that, the cell was cooled for 4 minutes while flowing a nitrogen / helium mixed gas. After cooling, the BET specific surface area of the sample was measured by the BET single point method using a Flow sorb II 2300 (manufactured by Shimadzu Corporation). In this case, the adsorption gas used during cooling and measurement was a mixed gas of 30 vol % nitrogen and 70 vol % helium.
[0060] <Evaluation of solid-state battery characteristics> (Battery Construction) All-solid-state batteries were produced using the electrode mixtures obtained in the examples and comparative examples. In this case, InLi foil was used as the counter electrode, and Li was used as the solid electrolyte. 5.4 P.S. 4.4 Cl 0.8 Br 0.8 The powder used was: The lower opening of a ceramic cylinder (opening diameter 10 mm) with open top and bottom was blocked with an electrode (made of SUS), 0.10 g of solid electrolyte was poured in, the upper opening was sandwiched between the electrodes, and uniaxial press molding was performed at 10 MPa to prepare an electrolyte layer. The upper electrode was removed once, the electrode mixture obtained in the examples and comparative examples was inserted, the upper electrode was reattached, and uniaxial press molding was performed at 42 MPa to press the positive electrode (electrode mixture) and the electrolyte layer. Next, the lower electrode was removed once, InLi foil was inserted, the lower electrode was reattached, and the upper and lower electrodes were screwed at four places with a torque pressure of 6 N·m to prepare an all-solid-state battery equivalent to 1.2 mAh. In this case, the preparation of the all-solid-state battery cell was performed in a glove box substituted with dry argon with an average dew point of -60°C.
[0061] (Evaluation of charge and discharge capacity) The capacity confirmation in the battery characteristic evaluation was performed by placing the all-solid-state batteries of the Examples and Comparative Examples in an environmental tester maintained at 25°C, connecting them to a charge / discharge measuring device, and evaluating them. Since the cell capacity is 1.2mAh, 1C is 1.2mA. The battery was charged and discharged at 0.1C up to 0.38V using the CCCV method (charging was terminated when the current value reached 0.01C), and the initial charge capacity ("Charge Capacity" in the table) was obtained. Discharge was performed at 0.1C using the CC method down to 2.38V, and the initial discharge capacity ("Discharge Capacity" in the table) was obtained.
[0062] (Evaluation of charge / discharge efficiency) The charge / discharge efficiency was obtained by inserting the initial discharge capacity and the initial charge capacity obtained above into the following formula. Charge / discharge efficiency (%) = (initial discharge capacity / initial charge capacity) x 100
[0063] [Table 1]
[0064] (Consideration) From the above-mentioned Examples and Comparative Examples and the results of the tests conducted by the present inventors, it is found that the titanium-niobium composite oxide as an active material (D 50 (μm) / BET(m2 It has been found that, while the solid electrolyte is such that the surface area ratio (R / g) is 0.005 or more and 5.0 or less, and, regarding the solid electrolyte, by forming an electrode mixture using a sulfide solid electrolyte containing lithium (Li), phosphorus (P), and sulfur (S) elements, a solid-state battery can be formed using the electrode mixture, which not only functions as a solid-state battery but also has excellent charge / discharge efficiency.
Claims
1. An electrode mixture comprising a sulfide solid electrolyte containing lithium (Li), phosphorus (P) and sulfur (S) elements, and an active material, The sulfide solid electrolyte is a crystalline material having an argyrodite-type crystal structure, The active material has the general formula Ti 1±α Nb 2±β O 7±γ (wherein, 0≦α<1, 0≦β<2, 0≦γ<0.3), a ratio (Nb / P) of the niobium (Nb) content (mol) of the active material to the phosphorus (P) content (mol) of the sulfide solid electrolyte is 1 or more and 173 or less; the sulfide solid electrolyte has a particle diameter D 50 at which the volume cumulative particle diameter becomes 50% according to a volume-based particle size distribution measured by a laser diffraction scattering particle size distribution measurement method, which is 3% to 50% of the active material's particle diameter D 50 at which the volume cumulative particle diameter becomes 50% according to a volume-based particle size distribution measured by a laser diffraction scattering particle size distribution measurement method; The active material has a particle diameter D relative to a BET specific surface area (BET) analyzed by a gas adsorption isotherm according to a multilayer adsorption theory. 50 The ratio (D 50 (μm) / BET(m 2 / g) is 0.005 or more and 5.0 or less.
2. The active material has a particle size D 50 The electrode mixture according to claim 1, wherein the average particle size is 0.1 μm or more and 8.0 μm or less.
3. The active material has a BET specific surface area of 1.0 m 2 / g or more 20m 2 The electrode mixture according to claim 1 or claim 2, wherein the electrode mixture has a viscosity of 1000:1 or less.
4. The active material has a particle size D 50 and a particle diameter D at which the volume cumulative particle diameter becomes 90% according to a volume-based particle size distribution measured by a laser diffraction scattering type particle size distribution measurement method. 90 and the particle diameter D at which the volume cumulative particle diameter becomes 10% 10 Relationship with (D 90 (μm)-D 10 (μm)) / D 50 (μm)=0.8~1.5 The electrode mixture according to claim 1 , which satisfies the following:
5. The active material has an average particle size D calculated by software analysis of particles in a scanning electron microscope image. SEM The particle size D 50 The ratio (D 50 (μm) / D SEM The electrode mixture according to any one of claims 1 to 4, wherein the average particle diameter (μm) is 1.0 or more and 3.5 or less.
6. The active material has an average particle size D calculated by software analysis of particles in a scanning electron microscope image. SEM The electrode mixture according to claim 1 , wherein the average particle size is 0.1 μm or more and 3.0 μm or less.
7. An electrode layer comprising the electrode mixture according to claim 1 .
8. A solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, A solid-state battery, wherein the positive electrode layer or the negative electrode layer comprises the electrode mixture according to claim 1 .
Citation Information
Patent Citations
Negative electrode material for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery using it
JP2010287496A
Active material for battery use, nonaqueous electrolyte battery, battery pack, and method for manufacturing active material for battery use
JP2014209442A
Active substance material for batteries, method for manufacturing the same, nonaqueous electrolyte battery, battery pack and motor vehicle
JP2015088467A
Method for manufacturing titanium niobium oxide negative electrode active material
JP2016219355A
Electrochemical cell, method for producing electrochemical cell, battery pack, and vehicle
WO2013140565A1
